Respuesta :

Answer:

m= -12

Step-by-step explanation:

-15m-30=-12m+6

-3m=36

m=-12

Answer:

m = -12

Step-by-step explanation:

Simplify the Left Hand Side:

[tex]-5\left(3m+6\right) = -5\cdot \:3m+\left(-5\right)\cdot \:6[/tex]

[tex]=-15m-30[/tex]

Simplify the Right Hand Side:

[tex]-3\left(4m-2\right)=-3\cdot \:4m-\left(-3\right)\cdot \:2[/tex]

[tex]=-3\cdot \:4m+3\cdot \:2[/tex]

[tex]= -12m+6[/tex]

All together we have:

[tex]-15m-30=-12m+6[/tex]

Add 30 to both sides and simplify:

[tex]-15m-30+30=-12m+6+30[/tex]

[tex]-15m=-12m+36[/tex]

Add 12m to both sides and simplify:

[tex]-15m+12m=-12m+36+12m[/tex]

[tex]-3m=36[/tex]

Finally, we divide both sides by -3:

[tex]\frac{-3m}{-3}=\frac{36}{-3}[/tex]

And we get the answer

m = -12

ACCESS MORE